Conserved role of spike S2 domain N-glycosylation across betacoronaviruses - Qi Yang; Anju Kelkar; Balaji Manicassamy; Sriram Neelamegham (npj Viruses)
Abstract Besides acting as an immunological shield, the N-glycans of SARS-CoV-2 are also critical for viral life cycle. As the S2 subunit of spike is highly conserved across betacoronaviruses, we determined the functional significance of the five ‘stem N-glycans’ located in S2 between N1098-N1194. Studies were performed with 31 Asn-to-Gln mutants, betacoronavirus virus-like particles and single-cycle viral replicons. Deletions of stem N-glycans enhanced S1 shedding from trimeric spike, reduced ACE2 binding and abolished syncytia formation. When three or more N-glycans were deleted, spike expression on cell surface and incorporation into virions was both reduced. Viral entry function was progressively lost upon deleting the N1098 glycan in combination with additional glycosite modifications. In addition to SARS-CoV-2, deleting stem N-glycans in SARS-CoV and MERS-CoV spike also prevented viral entry into target cells. These data suggest multiple functional roles for the stem N-glycans, and evolutionarily conserved properties for these complex carbohydrates across human betacoronaviruses.